2022
DOI: 10.1073/pnas.2201862119
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus infects brain microvascular endothelial cells, crosses the blood–brain barrier, and invades the central nervous system

Abstract: Hepatitis E virus (HEV) is an important but understudied zoonotic virus causing both acute and chronic viral hepatitis. A proportion of HEV-infected individuals also developed neurological diseases such as Guillain–Barré syndrome, neuralgic amyotrophy, encephalitis, and myelitis, although the mechanism remains unknown. In this study, by using an in vitro blood–brain barrier (BBB) model, we first investigated whether HEV can cross the BBB and whether the quasi-enveloped HEV virions are more permissible to the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…This hypothesis is supported by the association between a high level of intrahost HEV diversity (in ORF1 and ORF2 regions) and evolution toward chronic hepatitis E. 18 , 25 In addition, a compartmentalization of HEV quasi-species was observed between the blood and cerebrospinal fluid in patients with chronic hepatitis E. 26 , 27 Such compartmentalization argue for extrahepatic HEV replication in the central nervous system, in line with other clinical and in vitro studies. 28 , 29 , 30 Recent studies suggested that HEV could also replicate in human intestines. Indeed, HEV can replicate in enterocytes in vitro and be detected in intestinal tissue samples from patients with chronic HEV infection.…”
mentioning
confidence: 99%
“…This hypothesis is supported by the association between a high level of intrahost HEV diversity (in ORF1 and ORF2 regions) and evolution toward chronic hepatitis E. 18 , 25 In addition, a compartmentalization of HEV quasi-species was observed between the blood and cerebrospinal fluid in patients with chronic hepatitis E. 26 , 27 Such compartmentalization argue for extrahepatic HEV replication in the central nervous system, in line with other clinical and in vitro studies. 28 , 29 , 30 Recent studies suggested that HEV could also replicate in human intestines. Indeed, HEV can replicate in enterocytes in vitro and be detected in intestinal tissue samples from patients with chronic HEV infection.…”
mentioning
confidence: 99%
“…Notably, the virus strains we used here are all wild-type HEVs isolated from stool samples of hepatitis E patients or infected animals, and wild-type strains are known to be extremely difficult to culture in cells. Previous studies frequently used the Kernow-C1 p6 cloned virus for in vitro replication/infection [ 10 , 14 ]. It seems that this strain has a more favorable in vitro growth efficiency in hepatic cells or extrahepatic cells than wild-type HEVs.…”
Section: Discussionmentioning
confidence: 99%
“…During chronic HEV infection, HEV replicates more efficiently under immunosuppressant treatment and extrahepatic replication and manifestations can frequently occur [ 4 , 5 ]. HEV replication outside of the liver and hepatocytes has been reported in cell culture models, including neuronal [ 6 ], renal [ 7 ] and placental cell lines [ 8 ], as well as in tissues of hepatitis E patients or experimentally infected animals such as kidney [ 9 ], brain [ 10 ], cerebrospinal fluid [ 11 ], urine [ 12 ], placenta [ 13 ] and intestine [ 14 ]. In recent years, the presence of HEV in human semen samples has aroused broad interest in the field.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that some individuals infected with HEV also experience neurological complications such as Guillain-Barré syndrome, neuralgic amyotrophy, encephalitis, and myelitis [63][64][65][66][67]. As CI-2018QH was detected in the brain tissue of a Cricetulus longicaudatus, to confirm the probable neurologic tropism, we had attempted isolation of the virus by intracranial inoculation of 3-day-old ICR suckling mice with WL30G and WL48G specimens.…”
Section: Discussionmentioning
confidence: 99%